The Impact of Uncertainty and Financial Shocks in Recessions and Booms - Leonard Salzmann (ZBW - Leibniz Information Centre for Economics, 2020)
The literature has widely discussed the role of financial and economic uncertainty shocks for the macroeconomy. However, it has turned out to be difficult to isolate these shocks from financial market indicators and uncertainty proxies because any identifying restriction on their response profile requires strong assumptions. To obtain more robust results, I model financial and uncertainty shocks jointly in a state-dependent FAVAR setup for the U.S. and provide agnostic identification bounds on their effects. I document that (i) uncertainty shocks are of limited relevance for real activity and asset prices in boom periods but have significantly contractionary effects in recessions. (ii) By comparison, adverse financial shocks are contractionary both in recessions and boom periods. (iii) Identifying assumptions play a significant role in the effect magnitudes, especially for uncertainty shocks and in recessions. (iv) Financial conditions are generally a key transmission channel of uncertainty shocks. (v) Uncertainty transmits financial shocks to a noticeable degree in recessions.
Keywords: E32; E37; E44; 330; Macroeconomic tail events; nonlinear FAVARs; uncertainty shocks; financial shocks